2004
DOI: 10.1529/biophysj.104.046466
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding of Ubiquitin Studied by Picosecond Time-Resolved Fluorescence of the Tyrosine Residue

Abstract: The photophysics of the single tyrosine in bovine ubiquitin (UBQ) was studied by picosecond time-resolved fluorescence spectroscopy, as a function of pH and along thermal and chemical unfolding, with the following results: First, at room temperature (25 degrees C) and below pH 1.5, native UBQ shows single-exponential decays. From pH 2 to 7, triple-exponential decays were observed and the three decay times were attributed to the presence of tyrosine, a tyrosine-carboxylate hydrogen-bonded complex, and excited-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 28 publications
5
25
1
Order By: Relevance
“…Above this water content, a second shorter decay time (;400 ps) starts to develop and its normalized preexponential ultimately reaches the value of 0.12 in water (9). Very similar observations were made with the single-tyrosine protein UBQ, but the preexponential value was greater (5). The observation of this double-exponential decay, which results from electron transfer from one of the three cresol rotamers to the protein backbone, depends on three factors: i), the relative mol fractions of the ground-state rotamer population, the rotamer conformations being determined by rotation about the C a -C b bond (a); ii), the rotational rate constants for interconversion between the rotamers, k r and k r 9; and iii), the photo-induced electron transfer rate constant, k ET , which depends strongly on solvent polarity (9).…”
Section: Fluorescence Decays Of Rnase Asupporting
confidence: 66%
See 3 more Smart Citations
“…Above this water content, a second shorter decay time (;400 ps) starts to develop and its normalized preexponential ultimately reaches the value of 0.12 in water (9). Very similar observations were made with the single-tyrosine protein UBQ, but the preexponential value was greater (5). The observation of this double-exponential decay, which results from electron transfer from one of the three cresol rotamers to the protein backbone, depends on three factors: i), the relative mol fractions of the ground-state rotamer population, the rotamer conformations being determined by rotation about the C a -C b bond (a); ii), the rotational rate constants for interconversion between the rotamers, k r and k r 9; and iii), the photo-induced electron transfer rate constant, k ET , which depends strongly on solvent polarity (9).…”
Section: Fluorescence Decays Of Rnase Asupporting
confidence: 66%
“…Studies carried out by Wills and Szabo (19) demonstrated that the fluorescence of Tyr is quenched in the presence of hydrogen-bond acceptors such as acetate. We have made a similar observation for Tyr in UBQ, whose fluorescence is quenched as a result of proton transfer to a nearby carboxylate group of Glu-51 (5). Since previous studies have suggested that, at pH 5, Tyr-25 of RNase A is hydrogen-bonded to the carboxylate of Asp-14 (7,20), we have analyzed the fluorescence response to the pH change.…”
Section: Absorption and Steady-state Fluorescence Of Rnase Asupporting
confidence: 59%
See 2 more Smart Citations
“…The proton of Tyr in the excited state may be transferred to carboxyl of the Glu residue or Asp residue, if the two residues are located near Tyr. 34 At pH 7.4, Ser166 of EoCen can be phosphorylated by PKA. The introduced phosphate group at Ser166 located near Tyr168 becomes negatively charged.…”
Section: Fluorescence Lifetime Measurements Of Eocen and Eocenpmentioning
confidence: 99%